Estimating "Gamma" for Tail-hedge Discount Rates When Project Returns Are Co-integrated with GDP - Lars Hultkrantz; Panagiotis Mantalos (Örebro University School of Business, 2016)
Weitzman (2012, 2013) has suggested a method for calculating social discount rates for long-term investments when project returns are covariant with consumption or other macroeconomic variables, so called "tail-hedge discounting". This method relies on a parameter called "real project gamma" that measures the proportion of project returns that is covariant with the macroeconomic variable. We suggest two approaches for estimation of this gamma when the project returns and the macroeconomic variable are co-integrated. First we use Weitzman's (2012) own approach, and second a simple data transformation that keeps gamma within the zero to one interval. In a Mont-Carlo study we show that the method of using a standardized series is better and robust under different data-generating processes. Both approaches are demonstrated in a Monte-Carlo experiment and applied to Swedish time-series data from 1950-2011 for annual time-series data for rail freight (a measure of returns from rail investments) and GDP.
Keywords: D61; D90; G11; H43; R42; 330; GDP; social rate of discount; tail-hedge discounting; cost-benefit analysis; real-project gamma